Arterial Spin Labeling Imaging for the Parotid Glands of Patients with Sjögren’s Syndrome - Kami, Yukiko N.; Sumi, Misa; Takagi, Yukinori; Sasaki, Miho; Uetani, Masataka; Nakamura, Takashi (PLOS ONE, 2016)
Sjögren’s syndrome (SS) is characterized by hypofunction of the salivary and lacrimal glands. The salivary function is largely dependent upon the blood supply in the glands. However, the diseased states of the gland perfusion are not well understood. The arterial spin labeling (ASL) technique allows noninvasive quantitative assessment of tissue perfusion without the need for contrast agent. Here, we prospectively compared the perfusion properties of the parotid glands between patients with SS and those with healthy glands using ASL MR imaging. We analyzed salivary blood flow (SBF) kinetics of 22 healthy parotid glands from 11 volunteers and 28 parotid glands from 14 SS patients using 3T pseudo-continuous ASL imaging. SBF was determined in resting state (base SBF) and at 3 sequential segments after gustatory stimulation. SBF kinetic profiles were characterized by base SBF level, increment ratio at the SBF peak, and the differences in segments where the peak appeared (SBF types). Base SBFs of the SS glands were significantly higher than those of healthy glands (59.2 ± 22.8 vs. 46.3 ± 9.0 mL/min/100 g, p = 0.01). SBF kinetic profiles of the SS glands also exhibited significantly later SBF peaks (p < 0.001) and higher SBF increment ratios (74 ± 49% vs. 47 ± 39%, p = 0.04) than the healthy glands. The best SBF criterion (= 51.2 mL/min/100 mg) differentiated between control subjects and SS patients with 71% sensitivity and 82% specificity. Taken together, these results showed that the SS parotid glands were mostly hyperemic and the SS gland responses to gustatory stimulation were stronger and more prolonged than those of the healthy glands. The ASL may be a promising technique for assessing the diseased salivary gland vascularization of SS patients.